Pure word deafness with auditory object agnosia after bilateral lesion of the superior temporal sulcus - Gutschalk, Alexander; Uppenkamp, Stefan; Riedel, Bernhard; Bartsch, Andreas J.; Brandt, Tobias; Vogt-Schaden, Maria-Elisabeth (Cortex, 2015)
Based on results from functional imaging, cortex along the superior temporal sulcus (STS) has been suggested to subserve phoneme and pre-lexical speech perception. For vowel classification, both superior temporal plane (STP) and STS areas have been suggested relevant. Lesion of bilateral STS may conversely be expected to cause pure word deafness and possibly also impaired vowel classification. Here we studied a patient with bilateral STS lesions caused by ischemic strokes and relatively intact medial STPs to characterize the behavioral consequences of STS loss. The patient showed severe deficits in auditory speech perception, whereas his speech production was fluent and communication by written speech was grossly intact. Auditory-evoked fields in the STP were within normal limits on both sides, suggesting that major parts of the auditory cortex were functionally intact. Further studies showed that the patient had normal hearing thresholds and only mild disability in tests for telencephalic hearing disorder. Prominent deficits were discovered in an auditory-object classification task, where the patient performed four standard deviations below the control group. In marked contrast, performance in a vowel-classification task was intact. Auditory evoked fields showed enhanced responses for vowels compared to matched non-vowels within normal limits. Our results are consistent with the notion that cortex along STS is important for auditory speech perception, although it does not appear to be entirely speech specific. Formant analysis and single vowel classification, however, appear to be already implemented in auditory cortex on the STP.
Gesehen am 16.02.2021